Metabolic and Biomolecular Changes Induced by Incremental Long-Term Training in Young Thoroughbred Racehorses during First Workout Season - Miglio, Arianna (Animals (Basel), 2020)
SIMPLE SUMMARY: Sport training leads to adaptation to physical effort that is reflected by changes in blood parameters. The Thoroughbred racehorse is a valid animal model to investigate such changes. Twenty-nine clinically healthy, two-year-old Thoroughbred racehorses were followed during their first 4-month sprint training. Blood collection was performed at rest, once a month, five times. For each sample, blood parameters were determined. Moreover, before the beginning and at the end of the experimental period, serum protein electrophoresis and genetic analysis to evaluate the expression of key genes related to inflammatory and immunity responses were performed on all samples. Significant modifications were identified compared with the beginning of training for numerous metabolites and genes related to immunity response. In conclusion, the first long-term training period induces fundamental systemic changes in untrained Thoroughbreds probably as the result of the onset of physiologic adaptation to training. ABSTRACT: Training has a huge effect on physiological homeostasis. The Thoroughbred racehorse is a valid animal model to investigate such changes for training schedule fine-tuning. As happens in human athletes, it is hypothesized that biochemical and immune response changes and related biomolecular variations could be induced by training programs. The aim of this study was to investigate, for the first time, the long-term metabolic and biomolecular modifications in young untrained Thoroughbred racehorses in the first 4-month timeframe training period. Twenty-nine clinically healthy, untrained, two-year-old Thoroughbred racehorses were followed during their incremental 4-month sprint exercise schedule. Blood collection was performed once a month, five times (T-30, T0, T30, T60, and T90). For each sample, lactate concentration, plasma cell volume (PCV), and hematobiochemical parameters (glucose, urea, creatinine, aspartate aminotransferase (AST), γ-glutamyltransferase (GGT), alkaline phosphatase (ALP), total bilirubin (Tbil), lactate dehydrogenase (LDH), creatine kinase (CK), cholesterol, triglycerides, albumin (Alb), total proteins (TPs), phosphorus (P), calcium (Ca(2+)), magnesium (Mg), sodium (Na(+)), potassium (K(−)), and chloride (Cl)) were determined. At T-30 and T90, serum protein electrophoresis (SPE), serum amyloid A (SAA), and real-time qPCR were performed on all samples to evaluate the expression of key genes and cytokines related to inflammatory and Th2 immunity responses: Interleukin-4 (IL-4), Interleukin-6 (IL-6), Interleukin-10 (IL-10), Interleukin-1β (IL-1β), Octamer-Binding Transcription Factor 1 (OCT1), B-cell lymphoma/leukemia 11A (BCL11A). Statistical analysis was performed (ANOVA and t test, p < 0.05). Significant modifications were identified compared with T-30 for PCV, glucose, triglycerides, cholesterol, lactate, urea, creatinine, Tbil, ALP, LDH, Na(+), K(−), Ca(2+), SAA, TPs, SPE, IL-6, IL-4, Oct-1, and BCL11A. In conclusion, the first long-term training period was found to induce fundamental systemic changes in untrained Thoroughbreds.